PENGEMBANGAN TRAINER KIT INSTALASI PENERANGAN LISTRIK DENGAN PELENGKAP SENSOR DI SMK NEGERI 1 SEDAYU - Sony Joko Wahono; Sukir Sukir (JPTE FT UNY, 2020)
ABSTRACT:This study aims to: (1) produce an electric lighting installation trainer kit with a complement to sensors on the subject of Electrical Lighting Installation, (2) knowing the feasibility of an electric lighting installation trainer kit with sensor attachments in the Electrical Lighting Installation subject. This research is a Research and Development study using the ADDIE method with the stages of Analysis, Design, Development, Implementation, and Evaluation. This research was conducted at Vocational High School 1 Sedayu with the subjects: material experts, media experts, and 30 Electrical Power Installation Engineering students. The data analysis technique used is descriptive analysis. The data collection technique uses a questionnaire. The results of this study in terms of the feasibility of the electric lighting installation trainer kit based on the results of the assessment in terms of media, material aspects, and student users get the results, namely the media expert's assessment obtained an average score of 68 and categorized as highly feasible. The material obtained an average score of 63.5 and categorized as highly feasible, the student user assessment obtained an average score of 85.23 and categorized as highly feasible.ABSTRAK:Penelitian ini bertujuan untuk : (1) menghasilkan trainer kit instalasi penerangan listrik dengan pelengkap sensor pada mata pelajaran Instalasi Penerangan Listrik, (2) mengetahui kelayakan trainer kit instalasi penerangan listrik dengan pelengkap sensor pada mata pelajaran Instalasi Penerangan Listrik. Penelitian ini merupakan penelitian Research and Developtment dengan metode ADDIE dengan tahapan Analysis, Design, Development, Implementation, dan Evaluation. Penelitian ini dilakukan di SMK N 1 Sedayu dengan subjek : ahli materi, ahli media dan 30 siswa Teknik Instalasi Tenaga Listrik. Teknik analisis data yang digunakan adalah analisis deskriptif. Teknik pengumpulan data menggunakan angket Hasil dari penelitian ini ditinjau dari segi kelayakan trainer kit instalasi penerangan listrik berdasarkan hasil penilaian dari segi media, segi materi, dan pengguna siswa mendapatkan hasil yaitu penilaian ahli media diperoleh skor rata-rata 68 dengan kategori sangat layak, penilaian ahli materi diperoleh skor rata-rata 63,5 dengan kategori sangat layak, penilaian pengguna siswa diperoleh skor rata-rata 85,23 dengan kategori sangat layak.